Pengaruh Kualitas Produk Terhadap Tingkat Kepuasan Konsumen dalam Perspektif Islam di Kios Joyo Mulyo Pasar Tradisional Pandaan, Pasuruan - Leli Dwi Agustining Tias; M. Dayat; Ifdholul Maghfur (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study examines the effect of product quality on Muslim consumer satisfaction at Kios Joyo Mulyo, Pandaan, Pasuruan. Product quality is measured through aesthetics, durability, specialty, and customization. Consumer satisfaction is assessed from functional aspects, benefits, and Islamic values ​​such as blessings and halalness. Using quantitative methods and surveys on 93 Muslim consumers, this study analyzed the data with multiple linear regression. The results showed that product durability, specialty, and balance had a positive and significant effect on consumer satisfaction. Product aesthetics did not show a statistically significant effect. Simultaneously, the four dimensions of product quality explained 57.8% of the variation in consumer satisfaction.